2014
DOI: 10.1186/1471-2164-15-1074
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of the lesser spotted catshark (Scyliorhinus canicula) pancreas, liver and brain reveals molecular level conservation of vertebrate pancreas function

Abstract: BackgroundUnderstanding the evolution of the vertebrate pancreas is key to understanding its functions. The chondrichthyes (cartilaginous fish such as sharks and rays) have often been suggested to possess the most ancient example of a distinct pancreas with both hormonal (endocrine) and digestive (exocrine) roles. The lack of genetic, genomic and transcriptomic data for cartilaginous fish has hindered a more thorough understanding of the molecular-level functions of the chondrichthyan pancreas, particularly wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 131 publications
2
18
0
Order By: Relevance
“…Thus, although lampreys do not possess a distinct pancreatic gland similar to jawed vertebrates, most of the genes associated with the Pdxnetwork of jawed vertebrate pancreas are present and expressed in the islet organ of lampreys. A previous study had shown that cartilaginous fishes possess a three-hormone (insulin, glucagon, and somatostatin) pancreas and that the four-hormone (the three plus pancreatic polypeptide) pancreas found in coelacanth and tetrapods was a later innovation (39). The brook lamprey pancreas RNA-seq data includes transcripts (SI Appendix) for the three hormones present in the pancreas of cartilaginous fishes, indicating that the three hormone pancreas had evolved in the common ancestor of all vertebrates.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, although lampreys do not possess a distinct pancreatic gland similar to jawed vertebrates, most of the genes associated with the Pdxnetwork of jawed vertebrate pancreas are present and expressed in the islet organ of lampreys. A previous study had shown that cartilaginous fishes possess a three-hormone (insulin, glucagon, and somatostatin) pancreas and that the four-hormone (the three plus pancreatic polypeptide) pancreas found in coelacanth and tetrapods was a later innovation (39). The brook lamprey pancreas RNA-seq data includes transcripts (SI Appendix) for the three hormones present in the pancreas of cartilaginous fishes, indicating that the three hormone pancreas had evolved in the common ancestor of all vertebrates.…”
Section: Discussionmentioning
confidence: 97%
“…Since then, NPY has been one of the most studied appetite-regulating hormones in fish. It has been cloned and/or shown to regulate feeding in several groups, including Characiformes (Pereira et al, 2015), Cypriniformes [(e.g., goldfish, zebrafish (Yokobori et al, 2012), blunt snout bream Megalobrama amblycephala (Xu et al, 2016), grass carp Ctenopharyngodon idellus (Jin et al, 2015), Jian carp ( Cyprinus carpio ) (Tang et al, 2014), Ya fish (Wei et al, 2014)], Gadiformes (Atlantic cod Kortner et al, 2011; Tuziak et al, 2014); Gonorynchiformes (milkfish Chanos chanos , Lin et al, 2016); Perciformes (yellowtail Seriola quinqueradiata Hosomi et al, 2014, Astatotilapia burtoni Grone et al, 2012, cunner Tautogolabrus adspersus Babichuk and Volkoff, 2013, orange-spotted grouper Epinephelus coioides Tang et al, 2013, sea bass Leal et al, 2013, mandarin fish, Siniperca chuatsi Sun et al, 2014, cobia Rachycentron canadum Van Nguyen et al, 2013, gourami Trichogaster pectoralis Boonanuntanasarn et al, 2012); Pleuronectiformes (olive flounder Wang et al, 2015, winter flounder MacDonald and Volkoff, 2009a, Brazilian flounder Paralichthys orbignyanus Campos et al, 2012), Salmoniformes (e.g., rainbow trout Oncorhynchus mykiss Aldegunde and Mancebo, 2006, Atlantic salmon Valen et al, 2011; Kim et al, 2015), Siluriformes (channel catfish, Peterson et al, 2012; Schroeter et al, 2015); Tetraodontiformes (tiger puffer Takifugu rubripes Kamijo et al, 2011) as well as elasmobranchs [(e.g., winter skate Leucoraja ocellata , Rajiforme (MacDonald and Volkoff, 2009b) and spotted catshark ( Scyliorhinus canicula , Carcharhiniforme) Mulley et al, 2014)] and holocephalans (elephant fish Chimaeriformes; Larsson et al, 2009). The majority of these studies indicate that NPY has a widespread distribution and is present in both brain and intestinal tract, that it acts as an orexigenic factor and that its expression is affected by feeding and fasting.…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…There are a larger number of transcriptomic and RNA-seq studies, however, these genetic resources are still limited compared to those of other vertebrate taxa [ 27 ]. Transcriptome sequence examples include a heart transcriptome of the white shark [ 29 ]; brain, liver, pancreas, and embryo from the small-spotted catshark, S. canicula , [ 30 , 31 ]; an embryo of cloudy catshark, Scyliorhinus torazame [ 32 ]; whole embryo from the little skate [ 28 ]; and spleen and thymus from nurse shark, Ginglymostoma cirratum [ 26 ] and spleen, thymus, testis, ovary, liver, muscle, kidney, intestine, heart, gills, and brain from elephant shark (a holocephalan), C. milii [ 26 ]. In addition, EST (expressed sequence tag) sequences exist for cell lines derived from L. erinacea and the spiny dogfish, Squalus acanthias [ 33 ].…”
Section: Introductionmentioning
confidence: 99%